2023
DOI: 10.1186/s12905-023-02511-z
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with uptake of human papilloma virus vaccine among school girls aged 9–14 years in Lira City northern Uganda: a cross-sectional study

Abstract: Background Cervical cancer is the most common Human Papilloma Virus (HPV)-related disease among women. Since 2008, HPV vaccination has been routinely recommended for pre-adolescent and adolescent girls in Uganda as the primary preventive measure for cervical cancer. However, in Uganda, most especially in Lira district, there is limited literature on HPV vaccination uptake and associated factors among girls aged 9-14years. This study assessed the uptake of HPV vaccine and associated factors amon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…Global estimates suggest the rate of completion of the vaccine series is 15% [52]. Uptake of the vaccine was 19.6% in girls aged 9-14 in northern Uganda [53], 24.4% in general uptake in China [54], and 58.5% in girls aged 13-15 in the United States [55]. These data suggest that the economic status of the country may influence vaccine uptake.…”
Section: Vaccination Recommendations and Uptakementioning
confidence: 99%
“…Global estimates suggest the rate of completion of the vaccine series is 15% [52]. Uptake of the vaccine was 19.6% in girls aged 9-14 in northern Uganda [53], 24.4% in general uptake in China [54], and 58.5% in girls aged 13-15 in the United States [55]. These data suggest that the economic status of the country may influence vaccine uptake.…”
Section: Vaccination Recommendations and Uptakementioning
confidence: 99%
“…With regard to HPV vaccine coverages in these countries: (i) in the USA, according to the 2021 report on cancer-trend progress by the National Cancer Institute: 58.5% of adolescents aged 13-15 years had received two or three doses of HPV vaccines as recommended (https://progressreport.cancer.gov/prevention/hpv_ immunization, accessed on 16 November 2023); (ii) in China, according to 2020 estimates, vaccination coverage was <1%, and most HPV vaccines were given to adult women rather than to young girls aged 9-14 years old, though there is a plan to reach 90% vaccination in girls by the age of 15 in the year 2030 [30]. In Northern Uganda, Lira City, it was reported that about 19.6% of schoolgirls aged 9-14 years had received the HPV vaccine [31], which is a tiny portion of the country. According to a 2022 evaluation, Venezuela is one of the countries that have not introduced the HPV vaccine as a public health policy [32].…”
Section: Introductionmentioning
confidence: 99%